2020
DOI: 10.1055/s-0040-1701617
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Umbilical Cord Milking on Term Infants Delivered by Cesarean Section

Abstract: Objective Umbilical cord milking (UCM) is an efficient way to achieve optimal placental transfusion in term infants born by cesarean section (CS). However, it is not frequently performed due to concern for short-term adverse effects of increased blood volume, such as polycythemia and hyperbilirubinemia. The aim of this study is to evaluate the short-term effects of UCM on term infants delivered by CS. Study Design We conducted a pre- and postimplementation cohort study comparing term infants delivere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…10 Our previous study established the feasibility and safety of UCM in term infants delivered by cesarean section. 20 In a previously published randomized controlled trial, term infants who received DCC/UCM demonstrated lower residual placental volume and higher hemoglobin levels at 24 to 48 hours of life without an increase in hyperbilirubinemia or symptomatic polycythemia. 2 At 4 months of age, these infants had higher ferritin levels and increased brain myelin in the internal capsule and other early maturing brain regions associated with motor, visual, and sensory processing/function.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…10 Our previous study established the feasibility and safety of UCM in term infants delivered by cesarean section. 20 In a previously published randomized controlled trial, term infants who received DCC/UCM demonstrated lower residual placental volume and higher hemoglobin levels at 24 to 48 hours of life without an increase in hyperbilirubinemia or symptomatic polycythemia. 2 At 4 months of age, these infants had higher ferritin levels and increased brain myelin in the internal capsule and other early maturing brain regions associated with motor, visual, and sensory processing/function.…”
Section: Discussionmentioning
confidence: 93%
“…10 Our previous study established the feasibility and safety of UCM in term infants delivered by cesarean section. 20…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cord was then released at the placental end and allowed to refill with blood for a brief 1 to 3 seconds pause between each milking motion (12, 14, 18-24, 27, 29-36, 39-41, 42, 43, 45-49, 53, 58, 66, 69, 74, 76-78) . In general, the entire procedure was completed in not more than 30 s. After this, the umbilical cord was clamped and cut at 2-3 cm from the umbilicus and the infant taken to the warmer for routine newborn care (20,23,26,35,43,48,50,61,69,74,77) .…”
Section: Resultsmentioning
confidence: 99%
“…Several randomized controlled trials have demonstrated preterm infants delivered by C-section undergoing UCM vs. DCC had better systemic blood flow, blood pressure, hemoglobin levels, and urine output in the first 72 h of life ( 33 35 ). UCM has been found to be feasible in term infants born by C-section and did not result in higher incidence of phototherapy, symptomatic polycythemia, NICU hospitalizations, or readmissions for phototherapy ( 36 ). UCM may be a good alternative in elective C-section to optimize placental transfusion ( 37 ).…”
Section: Cord Management Strategiesmentioning
confidence: 99%